2006
DOI: 10.1111/j.1475-6773.2006.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Affairs Health System and Mental Health Treatment Retention among Patients with Serious Mental Illness: Evaluating Accessibility and Availability Barriers

Abstract: Objective. We examine the impact of two dimensions of access--geographic accessibility and availability--on VA health system and mental health treatment retention among patients with serious mental illness (SMI). Methods. Among 156,631 patients in the Veterans Affairs (VA) health care system with schizophrenia or bipolar disorder in fiscal year 1998 (FY98), we used Cox proportional hazards regression to model time to first 12-month gap in health system utilization, and in mental health services utilization, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 39 publications
6
84
2
Order By: Relevance
“…Veterans who live farther from VA facilities have been shown to be less likely to visit a VA pharmacy for prescriptions, receive a transplant, have radiation treatment, or use radiology or laboratory services at a VA facility than Veterans who live inside VA service areas or in urban areas French, Bradham, et al, 2012a;Patterson et al, 2014). In interviews, VA health care workers concurred with findings of prior studies reporting that although coordination and continuity of care within VA are generally good, challenges are faced by those who live far away (McCarthy et al, 2007;Skolarus et al, 2013). One study of Veterans with serious mental illness found that those who lived farther from VA had fewer visit days, but more visits per day, suggesting that Veterans who live farther away are more likely to "chain" appointments by scheduling more than one in a single day (McCarthy et al, 2006).…”
Section: Digital and Culturalsupporting
confidence: 75%
“…Veterans who live farther from VA facilities have been shown to be less likely to visit a VA pharmacy for prescriptions, receive a transplant, have radiation treatment, or use radiology or laboratory services at a VA facility than Veterans who live inside VA service areas or in urban areas French, Bradham, et al, 2012a;Patterson et al, 2014). In interviews, VA health care workers concurred with findings of prior studies reporting that although coordination and continuity of care within VA are generally good, challenges are faced by those who live far away (McCarthy et al, 2007;Skolarus et al, 2013). One study of Veterans with serious mental illness found that those who lived farther from VA had fewer visit days, but more visits per day, suggesting that Veterans who live farther away are more likely to "chain" appointments by scheduling more than one in a single day (McCarthy et al, 2006).…”
Section: Digital and Culturalsupporting
confidence: 75%
“…Thus future research should investigate whether organizational characteristics account for some variability in antipsychotic prescribing. For example, differences in availability of resources, staffing, quality improvement capability, program implementation, care coordination, and communication may affect provision of care (26,(31)(32)(33). The organization and provision of care have been shown to vary among VHA mental health programs, which may contribute to the observed variation (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Because the VHA has used electronic records for clinical care for many years, readily available administrative data sets can be used to identify and describe longitudinal antipsychotic prescribing pathways. Administrative data have been used extensively in other antipsychotic studies (11,20,(26)(27)(28). …”
Section: Setting and Data Sourcesmentioning
confidence: 99%
“…Two out of every five Veterans with serious mental illness experienced gaps in medical care lasting at least 12 months (4). Improving access to and continuity of health services may mitigate the health risks exacerbated by these gaps in care (3).…”
Section: Introductionmentioning
confidence: 99%